The effect of service quality on consumer satisfaction and loyalty at CV Farras Mobil in Demak Regency - Farras Khoirullah Kholil; Alifah Ratnawati (Privietlab, 2026)
This study aimed to analyze the effect of service quality on consumer satisfaction and loyalty at CV Farras Mobil in Demak Regency. Service quality in this study was measured using five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. This study also examines the role of consumer satisfaction as an intervening variable between service quality and consumer loyalty. This explanatory study employed a quantitative approach. The population consists of all consumers of CV Farras Mobil in Demak Regency, the exact number of which is unknown. Purposive sampling was used, with a total sample of 96 respondents included. Data were collected using a questionnaire and analyzed using multiple linear regression with the assistance of the SPSS version 29. The results show that the tangible variable has no effect on consumer satisfaction, whereas reliability has a positive and significant effect on consumer satisfaction. Responsiveness had no effect on consumer satisfaction, whereas assurance had a positive and significant effect on consumer satisfaction. Empathy also has no effect on consumer satisfaction. Furthermore, tangibles have no effect on consumer loyalty, and reliability also has no significant effect on consumer loyalty. However, responsiveness and assurance had positive and significant effects on consumer loyalty. Empathy had no effect on consumer loyalty, whereas consumer satisfaction had a positive and significant effect on consumer loyalty.